Rooting Out Hunger in Malawi with Nutritious Orange-Fleshed Sweetpotato - International Potato Center (2013)
By September 2013, the Malawi national program had released 6 pro-vitamin A rich, orange-fleshed sweetpotato (OFSP) varieties and over 100,000 households have received planting material by working with numerous development partners. OFSP is being integrated into the Scaling-Up Nutrition (SUN) effort to combat malnutrition at the community level.